NUMBER OF STEPS PER DAY AND PHYSICAL ACTIVITY LEVELS OF ADULTS IN GREECE - Maria Michalopoulou; Nikos Ageloussis; Labrini Drolapa; Stella Exarchopoulou (Exercise and Quality of Life, 2011)
This study compared self reported physical activity (PA) (MET min/week) withpedometer determined PA (steps/day). Participants in this study were 300 adults, (25 - 56 yearsof age). PA was assessed with the IPAQ long form and the number of steps was assessed withthe Yamax model SW-200. Participants wore the pedometer for 7 consecutive days. Data(categorical score) was analyzed using cross-tabs analysis. Two-way ANOVA (gender 2 x levelof PA 3) was performed on the number of steps/day. Significant main effect was reported onlyfor the factor ìlevel of PAî with adults in the moderate and the high activity group performingmore steps/day than adults in the low PA group. Adults in Greece performed less steps/day thanthe international recommendations PA suggest even though the majority of them were assignedby IPAQ long form at the moderate and very high PA groups.